Estudo de liberação de nanofibras poliméricas de Ecovio® contendo Cilostazol - Antunes, Lidiane Rodrigues (2020)
Peripheral arterial or vascular diseases are pathologies that affect the patient's normal arterial flow, causing obstruction of arteries or blood vessels, which can lead to ischemia. The drug Cilostazol is indicated for this class of patients who suffer from peripheral arterial diseases, and to improve the patient's quality of life. Thus, the study of nanofibers containing Cilostazol by means of the electrospinning technique becomes relevant, in order to obtain an alternative administration technology to the patient, which has milder side effects and is more practical and efficient to use. For this, a polymeric solution containing Cilostazol was prepared, which was electrophore using as solvents 85% v / v Chloroform and 15% v / v Dimethylformamide under magnetic stirring for one hour, in which Ecovio polymer was added to this solution. ® at 15% w / v. The concentration of Cilostazol was incorporated in the polymeric solution in the concentrations of 5% w / w, 10% w / w, 20% w / w and 30% w / w, in relation to the mass of the polymer. Drug in the phosphate buffer solution with a pH of 5.5, as well as the characterizations of the films obtained: analysis of optical and scanning electron microscopy (MO and SEM), infrared spectroscopy, thermogravimetry (TGA), exploratory differential calorimetry (DSC ) and X-ray diffraction (XRD). After obtaining the release curves, different kinetic models were adjusted, with the Peppas-Sahlin one showing the best results for R2 and for the Akaike criteria (AIC), that is, it obtained the best mathematical adjustment. The Peppas-Sahlin model demonstrates a greater mathematical contribution to the understanding of diffusion and relaxation phenomena when compared to the others Peppas’ models. Cilostazol showed a better release in the concentration of 30% (w / w), in which it occurred for a longer time and in a stable concentration. The results showed that this material has great potential to be used in the release of this drug.